The ocean calls : a haenyeo mermaid story - Cho, Tina M. (Kokila, 2020)
Wanting to follow in the footsteps of her free-diving haenyeo grandmother, a young Korean girl dutifully consumes her grandmother's strength-building abalone porridge and practices her breath control before suiting up and overcoming fears to make remarkable discoveries.